Patellar tendon properties distinguish elite from non-elite soccer players and are related to peak horizontal but not vertical power - Murtagh, Conall F. (Eur J Appl Physiol, 2018)
PURPOSE: To investigate potential differences in patellar tendon properties between elite and non-elite soccer players, and to establish whether tendon properties were related to power assessed during unilateral jumps performed in different directions. METHODS: Elite (n = 16; age 18.1 ± 1.0 years) and non-elite (n = 13; age 22.3 ± 2.7 years) soccer players performed vertical, horizontal-forward and medial unilateral countermovement jumps (CMJs) on a force plate. Patellar tendon (PT) cross-sectional area, elongation, strain, stiffness, and Young’s modulus (measured at the highest common force interval) were assessed with ultrasonography and isokinetic dynamometry. RESULTS: Elite demonstrated greater PT elongation (6.83 ± 1.87 vs. 4.92 ± 1.88 mm, P = 0.011) and strain (11.73 ± 3.25 vs. 8.38 ± 3.06%, P = 0.009) than non-elite soccer players. Projectile range and peak horizontal power during horizontal-forward CMJ correlated positively with tendon elongation (r = 0.657 and 0.693, P < 0.001) but inversely with Young’s modulus (r = − 0.376 and − 0.402; P = 0.044 and 0.031). Peak medial power during medial CMJ correlated positively with tendon elongation (r = 0.658, P < 0.001) but inversely with tendon stiffness (r = − 0.368, P = 0.050). CONCLUSIONS: Not only does a more compliant patellar tendon appear to be an indicator of elite soccer playing status but it may also facilitate unilateral horizontal-forward and medial, but not vertical CMJ performance. These findings should be considered when prescribing talent selection and development protocols related to direction-specific power in elite soccer players.